Steps towards green manufacturing through EDM process: A review. Issue 1 (31st December 2016) - Singh, Nishant K.; Pandey, Pulak M.; Singh, K.K.; Sharma, Manish K.
Abstract: This paper focuses on the current machining process initiatives, carried out by various researchers relevant to the environmental aspects, thereafter predicting EDM performances. electrical discharge machining (EDM) is widely used unconventional machining method, because of its ability to process very hard material with precision. In thermo-electric process, control spark generation between electrodes causes material removal; however, application of hydrocarbon oil based dielectric fluid is an issue of environmental disruption. Replacement of dielectric to rectify the problem is one of the main concerns in EDM research. This paper highlights dry-EDM, near-dry EDM and EDM in water, conceived as an environment friendly alteration in the oil EDM process referred as a green EDM process. The work provides a thorough review of dry, near-dry EDM and EDM in water as a process, where the target is to endeavor dielectric fluids which could be the alternative to replace hydrocarbon oil. It is perceived that water and gas based dielectrics could take over oil-based fluids in EDM applications. Novel technological advances in dry EDM machining processes, which deliberate the advanced stage of a technology in academic and industrial research is briefly reviewed and an outline for the future work has been paved.